A calculus problem by Akshat Sharda

Calculus Level 4

x 2 d y d x + y 2 exp ( x ( y x ) y ) = 2 y ( x y ) \large x^2\dfrac{dy}{dx}+y^2\exp\left(\frac{x(y-x)}{y}\right)=2y(x-y)

Solve the above differential equation.

Details

C C is a constant.

x ( x + y ) = y ln ( C e x + 1 ) x(x+y)=y\ln(Ce^x+1) x ( x + y ) = y ln ( C e x 1 ) x(x+y)=y\ln(Ce^x-1) x ( x y ) = y ln ( C e x 1 ) x(x-y)=y\ln(Ce^x-1) x 2 ( x + y ) = y ln ( C e x 1 ) x^2(x+y)=y\ln(Ce^x-1)

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Oct 14, 2017

If we put z = x ( y x ) y = x x 2 y z = \frac{x(y-x)}{y} = x - \frac{x^2}{y} then d z d x = 1 2 x y + x 2 y 2 d y d x \frac{dz}{dx} \; = \; 1 - \frac{2x}{y} + \frac{x^2}{y^2}\,\frac{dy}{dx} so the differential equation becomes e z = 2 x y 2 x 2 y 2 d y d x = d z d x 1 d x d z = 1 e z + 1 = e z e z + 1 x + c = ln ( e z + 1 ) C e x = e z + 1 z = ln ( C e x 1 ) x ( x y ) = y ln ( C e x 1 ) \begin{aligned} e^z & = \; \frac{2x}{y} - 2 - \frac{x^2}{y^2}\frac{dy}{dx} \; = \; -\frac{dz}{dx} - 1 \\ \frac{dx}{dz} & = \; -\frac{1}{e^z+1} \; = \; - \frac{e^{-z}}{e^{-z}+1} \\ x + c & = \; \ln\big(e^{-z}+1\big) \\ Ce^x & = \; e^{-z}+1 \\ -z & = \; \ln(Ce^x - 1) \\ x(x-y) & = \; y\ln(Ce^x-1) \end{aligned} putting C = e c C = e^c .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...